PENINGKATAN MUTU DOSEN DALAM PROSES PEMBELAJARAN DI UNIVERSITAS - Ilham Fahmi; Mohammad Fakry Gaffar; Johar Permana; Endang Herawan (Jurnal Administrasi Pendidikan, 2023)
This research aims to study and analyze in depth about improving the quality of lecturers in the learning process at the university which is focused on university policies and programs in improving lecturer qualifications and competencies in terms of seven quality elements. The method used is a qualitative method with a case study approach in 27 study programs at the University of Singaperbangsa Karawang, and involves elements of leadership, quality control units, lecturers and students as research participants. The results of this study indicate that the university has implemented policies and programs to improve the qualifications and competencies of lecturers, but overall the results have not shown superior quality in accordance with the quality standards of lecturers that have been set as a prerequisite in organizing a quality learning process at the university. Seven quality elements to improving lecturer qualifications and competencies namely quality philosophy, quality standards, quality policy objectives, quality structure, processes quality, quality control cycle and quality assessment, so that it increasingly meets the prerequisites for organizing a quality learning process.